2006
DOI: 10.1373/clinchem.2005.063032
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin, Adipocyte Fatty Acid Binding Protein, and Epidermal Fatty Acid Binding Protein: Proteins Newly Identified in Human Breast Milk

Abstract: Background: Breastfeeding may protect children from developing metabolic syndrome and other diseases later in life. We investigated novel proteins in human breast milk that might play a role in this process. We found a significant correlation between AFABP and EFABP concentrations (r ‫؍‬ 0.593, P <0.0001). Maternal EFABP concentrations were significantly higher in mothers who delivered boys than in those who delivered girls

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
69
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 41 publications
5
69
1
2
Order By: Relevance
“…In particular, maternal BMI was collected only in the Cincinnati cohort but was not a significant predictor of infant weight. However, we and others have reported a positive relationship between maternal BMI and milk adiponectin, 8,9 suggesting that adiponectin could act to limit the growth of babies born to overweight mothers.…”
Section: Woo Et Al 106mentioning
confidence: 55%
See 1 more Smart Citation
“…In particular, maternal BMI was collected only in the Cincinnati cohort but was not a significant predictor of infant weight. However, we and others have reported a positive relationship between maternal BMI and milk adiponectin, 8,9 suggesting that adiponectin could act to limit the growth of babies born to overweight mothers.…”
Section: Woo Et Al 106mentioning
confidence: 55%
“…Human milk contains adiponectin, an adipocyte-derived hormone, in quantities consistent with a potential physiologic effect (10-20 g/L). [7][8][9] High levels of circulating adiponectin are associated with less obesity and diabetes, and adiponectin plays significant roles in insulin sensitivity and fat metabolism. 10,11 Furthermore, adiponectin occurs in several oligomeric forms in serum, 12 of which the high-molecular-weight (HMW) form appears to be the most biologically active.…”
mentioning
confidence: 99%
“…They found positive correlations between BM leptin concentrations and body weight and between the BMI of mothers before pregnancy and at the time of delivery; leptin in BM also correlated with body weight gain during pregnancy. Bronsky et al (2006) found lower leptin concentrations in the BM of mothers who delivered preterm babies than in those who delivered at-term babies. Uysal et al (2002), using RIA, observed no significant difference in BM leptin concentrations between the mothers of obese and non-obese infants; BM leptin concentrations correlated with mother's BMI.…”
Section: Discussionmentioning
confidence: 73%
“…Weyermann et al (2006) observed that leptin concentration in BM correlated positively with leptin in maternal serum. In addition, Bronsky et al (2006) evaluated BM leptin concentration, but they applied the ELISA method. They found positive correlations between BM leptin concentrations and body weight and between the BMI of mothers before pregnancy and at the time of delivery; leptin in BM also correlated with body weight gain during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin and leptin -hormones produced by adipose tissue that are responsible for regulation of glucose and fatty acid metabolism and appetite -have recently been found to be secreted in breast milk. 31,32 Whether these hormones are expressed in breast tissue of nonlactating women remains unknown. Thus, while abdominal visceral obesity is known to contribute to the development of insulin resistance, 3,12 the additional action of hormonally active breast adipose tissue within this process requires elucidation.…”
mentioning
confidence: 99%